This looks like an elimination method problem.
-3x + 2y = -3
4x - y = -1
We need to add these two equations together to eliminate a variable. In the second problem, y is the easiest here, because it is negative, and it has no leading number on it.
My goal is when we add these two equations, the y's added up together add to 0.
-3x + 2y = -3
2(4x - y = -1)
Simplify:
-3x + 2y = -3
8x - 2y = -2
Now we add these equations together.
-3x + 2y = -3
8x - 2y = -2
------------------
5x + 0y = -5
Simplify: 5x = -5
Divide. x = -1
We can return to the start and plug in -1 for x now, so we can solve for y.
4x - y = -1
4(-1) - y = -1
-4 - y = -1
Add 4 to each side. -y = 3
Simplify: y = -3
We've now decided x = -1 and y = -3. We can plug these into each formula to verify that they work.
-3x + 2y = -3
4x - y = -1
-3(-1) + 2(-3) = -3
4(-1) - (-3) = -1
3 - 6 = -3? Yes
-4 + 3 = -1? Yes